INDONESIAN GRADUATE STUDENTS’ ATTRIBUTIONAL BELIEFS AND METACOGNITIVE STRATEGIES IN THE ACADEMIC READING COMPREHENSION - Elizabeth Emmanuela Sulistyawati; Concilianus Laos Mbato (International Journal of Humanity Studies (IJHS), 2021)
The field of students’ beliefs in reading comprehension has become an increasingly significant research issue in the educational context. However, there have been very few studies examining attributional beliefs and metacognitive strategies adopted by EFL graduate students to deal with comprehension skills and reading difficulties. Applying the attribution framework, this study aimed to fill in the gap by investigating students’ attributional beliefs, metacognitive reading strategies, and the correlation between attribution and metacognitive reading strategies. The researchers employed mixed-method research with questionnaires and interviews as the instruments to collect data. The results showed that the majority of students attributed their successes or failures to internal factors (efforts and strategies). Many students claimed that they often experienced reading difficulties during online learning. Lastly, the Pearson correlation showed that there was a strong correlation (r = 0.746) between attributional beliefs and metacognitive reading strategies. This study offers several implications for language learning, in particular, the academic reading comprehension. First, students need to have a higher awareness of attributional beliefs in academic reading. Second, language teachers should support students to develop internal attribution and metacognitive strategies in academic reading.